DOP87 Disease clearance as a new therapeutic target in patients with Ulcerative Colitis: A multicenter retrospective cohort study. (27th May 2021) - D'Amico, F; Fiorino, G; Massarini, E; Solitano, V; Guillo, L; Allocca, M; Furfaro, F; Zilli, A; Bonovas, S; Peyrin-Biroulet, L; Danese, S
Abstract: Background: Symptom control and endoscopic endoscopic healing have been the main treatment targets in patients with ulcerative colitis (UC). Recently, the concept of disease clearance has been proposed as a potential target in UC. We aimed to evaluate the impact of disease clearance on long-term outcomes in patients with UC. Methods: A multicenter retrospective cohort study was conducted at the Humanitas Research Hospital-IRCCS (Italy) and at the Nancy University Hospital (France) between January 2014 and February 2021. All consecutive adult patients with confirmed UC undergoing colonoscopy with biopsies and available histological reports and clinical data within one month of colonoscopy were eligible for inclusion. Disease clearance was defined as clinical (partial Mayo score ≤2 with no subscore >1), endoscopic (endoscopic Mayo score= 0), and histological (Nancy index= 0) remission of disease. The first available endoscopic procedure was considered as baseline. Disease clearance was measured at baseline and during follow-up by comparing the occurrence of negative disease outcomes in patients who achieved or not disease clearance. Results: A total of 302 patients were included (46.4% female). Disease clearance was detected in 42 patients (13.9%) at baseline. Median follow-up was 32.2 ± 20.2 months. No patient achieving disease clearance underwent surgery during follow-up compared with 22 subjects in the non-disease clearance group (0.0% vs 8.5%, p=0.1). Similarly, a lower hospitalization rate was detected in patients with disease clearance at baseline compared with the control group (7.1% vs 25.4%, p=0.01). Interestingly, 51/302 patients (16.9%) achieved both endoscopic and histologic remission. This subgroup experienced a significantly lower rate of hospitalization (7.8% vs 25.9%, p=0.008) and surgery (0.0% vs 8.8%, p=0.05) compared with patients with endoscopic and/or histologic disease activity. The Kaplan Meier curves confirmed that patients with disease clearance at baseline had a lower risk for surgery (p=0.04) and hospitalization (hazard ratio (HR)= 0.49, 95% confidence interval (CI) 0.08–2.29, p=0.009) (Figures 1–2). Conclusion: Disease clearance is a new outcome that simultaneously takes into account remission of symptoms, endoscopy and histology. Patients with disease clearance are at significant lower risk for hospitalization and surgery and could be the ultimate therapeutic target for full disease control.